UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL JAHE MERAH (ZINGIBER OFFICINALE VAR. RUBRUM) MENGGUNAKAN METODE DPPH - Hera Derliana Lumban Raja; Nerly Juli Pranita Simanjuntak; Erida Novriani (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Antioxidants play an important role in warding off free radicals that can cause oxidative stress and various degenerative diseases. One potential source of natural antioxidants is red ginger leaves ( Zingiber officinale var. rubrum ). This study aims to determine the antioxidant activity of ethanol extract of red ginger leaves using the DPPH method. Extraction was carried out using ethanol solvent, then the antioxidant activity was tested at various concentrations of 20, 30, 40, and 50 ppm. The parameters observed included absorbance value, inhibition percentage, and IC ₅₀ value . The results showed that the inhibition percentage increased with increasing extract concentration. The IC₅₀ value obtained was 45.50 ppm , indicating that the ethanol extract of red ginger leaves has very strong antioxidant activity. Based on these results, it can be concluded that red ginger leaves have the potential as a source of natural antioxidants that can be developed in the fields of health and functional foods.